Brandpunten in het geologisch onderzoek van oostelijk Centraal-Afrika - P. Van den Haute (Afrika Focus, 1985)
The present paper offers a general view of the geological history of central East Africa. It is meant to inform persons involved in all kinds of African research about the physical background of this enormous continent. As the text is intended for people with no specific training in the earth sciences, an extensive introductory part has been dedicated to the general principles and methods of historical geology. The principle of superposition and the meaning of a major unconformity are shortly explained. Also the significance of fossils and of radiometric dating is elucidated with respect to the reconstruction of geological history. Further on a general outline is given of the great mountain belts of the African continent dating back from thÃƒÂ© earliest geological times (Precambrian), followed by a more detailed discussion of these belts in central East Africa. As to the younger structures of this region, attention has been focused on the large elongated furrow known as the East African rift. The major characteristics of this important feature in the earth's crust are described and its genesis is briefly discussed.